Influence of Initial Imperfections on the Laterally Loaded Cylindrical Shell - Ondřej VOLTR; Jan PEŇÁZ (Transactions of the VŠB-Technical University of Ostrava, Mechanical Series, 2013)
The article deals with the assessment of influence of initial imperfection on the loss of stability of laterally loaded cylindrical shell. The studied structure is a simplified case of the horizontal cylindrical shell (road tank [1, 2]) located on saddle supports. The initial geometrical imperfection is situated in the vicinity of the saddle and it is considered as the state of preload of the saddle from the own weight of shell and its content’s weight. Change of reduction factor α in response to the change of geometrical parameters of numerical model (embracing angle 2ϑ, thickness of the shell t) is monitored in the article. In the context of changing reduction factor α process of deformation of shell is also observed in this article. Numerical analyses were performed by finite element method computer program COSMOS/M [3].